Job quality in the micro and small enterprise sector in Ethiopia: Evidence from firm-level data - Berihu Assefa Gebrehiwot (Cogent Economics & Finance, 2022)
Micro and small enterprises are ubiquitous in developing countries and play a central role in employment. While there is solid empirical evidence that micro and small enterprises are important drivers of job creation, there is limited evidence on the quality aspects of employment in this sector, particularly in developing countries. Much of the previous research has focused primarily on quantitative job creation. Some studies have investigated job quality using labor force survey data at the employee-level. However, these studies hardly examined the role of entrepreneurial and firm characteristics on job quality. Firms and entrepreneurs in the micro and small business sector are natural targets of policy initiatives to improve job quality. Cognizant of this, this research aims to examine the determinants of job quality in the micro and small business sector in Ethiopia. Using a large firm-level primary dataset collected in the 10 largest cities in Ethiopia, the paper examines the relationship between entrepreneurial characteristics and indicators of job quality. Our regression results show the existence of a positive and significant correlation between job quality, as measured by average wages and job security and safety indicators, and entrepreneurial education and experience, as well as firm size and the presence of a professionally recruited manager. Our findings offer some important implications for policymakers to improve job quality by identifying the entrepreneurial and firm characteristics that drive or constrain quality job creation in the formal micro and small business economy in urban contexts.
Keywords: J01; J33; J81; 330; entrepreneur; Ethiopia; job quality; manufacturing; MSE